The knowing body as a floating body. Issue 5 (November 2017) - Valtonen, Anu; Meriläinen, Susan; Laine, Pikka-Maaria; Salmela-Leppänen, Tarja
This article enriches practice-based studies on bodily knowing by conceptualizing the knowing body as a floating body. This concept accords epistemic value to two forms of bodily existence – waking and sleeping – that are considered to be intertwined and floating. Based on an auto-ethnographic study conducted in Finnish academia, we propose three different sensorial flows that the knowing body engages in when participating in organizational practices: sensory release, within-corporeality and sensory entanglement in dreams. These forms highlight the inconstant and uncertain nature of embodied knowing, suggesting a novel onto-epistemological stance in which the knowing body is thought of as a floating body that is never still. The study also has implications for management education.